Implementation of The Spice Route Program in Aceh Province: Opportunities and Challenges as a World Cultural Heritage - Syahroni, Faez; Pribadi, Ulung; Suranto, Suranto (Journal of Governance and Public Policy, 2023)
This study aims to see the implementation, opportunities, and challenges of the Spice Route program in Aceh Province as a world cultural heritage with several indicators, namely Bureaucratic Structure, Resources, Disposition, Communication, Program Content, and Context. A qualitative method with a case study approach and NVivo 12 Plus as a supporter of the analysis. The findings of this study indicate that the implementation of the Spice Route program in Aceh Province has not been fully running well, there are many weaknesses in terms of the bureaucratic structure and budgetary resources as well as human resources, commitments are still minimal, and do not meet standards. Furthermore, in terms of activities, it was found that there were still many activities that were ceremonial in nature and did not lead to physical activities, such as the construction of a spice botanical garden as a center for agro-tourism and agro-industry of Aceh spices. In terms of opportunities, it has excellent potential to be used as a world cultural heritage with historical evidence of its herbs and its location as a gateway to the Straits of Malacca and the Indian Ocean for international trade routes. In terms of challenges, there is no good cooperation between agencies, both vertical agencies and the Aceh government and the Aceh government and Regency / City Government.